Modelling of particulate matter concentrations and source contributions in the Helsinki Metropolitan Area in 2008 and 2010: - Aarnio, M.A.; Kukkonen, J.; Kangas, L.; Kauhaniemi, M.; Kousa, A.; Hendriks, C.; Yli-Tuomi, T.; Lanki, T.; Hoek, G.; Brunekreef, B.; Elolähde, T.; Karppinen, A. (Finnish Environment Institute, 2016)
We refined an urban-scale dispersion modelling system by adding a road dust suspension model, FORE. The deterministic modelling includes both vehicular exhaust emissions (including cold start and cold driving) and suspended road dust. The urban scale modelling system was used in combination with the regional scale chemical transport model LOTOSEUROS, for 2008, and the measured regional background concentrations, for 2010. The predictions were compared against measured concentrations of PM2.5 and PM10. PM2.5 concentrations were slightly and the PM10concentrations substantially under-predicted in 2008, mainly due to the under-predicted regional background concentration. Source contributions of suspended road dust varied from 2% to 8% and from 12% to 38% for PM2.5 and PM10, respectively. Long-range transported contributions at the urban traffic stations were 72% to 92% for PM2.5 and 50% to 83% for PM10. © 2016.